Declining Basal Motion Dominates the Long‐Term Slowing of Athabasca Glacier, Canada. Issue 10 (21st October 2022) - Armstrong, William H.; Polashenski, David; Truffer, Martin; Horne, Greg; Hanson, Jacob B.; Hawley, Robert L.; Hengst, Anthony M.; Vowels, Lily; Menounos, Brian; Wychen, Wesley Van
Abstract: Globally, glaciers are shrinking in response to climate change, with implications for global sea level rise as well as downstream ecosystems and water resources. Sliding at the ice‐bed interface (basal motion) provides a mechanism for glaciers to respond rapidly to climate change. While the short‐term dynamics of glacier basal motion (<10 years) have received substantial attention, little is known about how basal motion and its sensitivity to subglacial hydrology changes over long (>50 year) timescales—this knowledge is required for accurate prediction of future glacier change. We compare historical data with modern estimates from field and satellite data at Athabasca Glacier and show that the glacier thinned by 60 m (−21%) over 1961–2020. However, a concurrent increase in surface slope results in minimal change in the average driving stress (−6 kPa and −4%). These geometric changes coincide with relatively uniform slowing (−15 m a −1 and −45%). Simplified ice modeling suggests that declining basal motion accounts for most of this slow down (91% on average and 46% at minimum). A decline in basal motion can be explained by increasing basal friction resulting from geometric change in addition to increasing meltwater flux through a more efficient subglacial hydrologic system. These results highlight the need to include time‐varying dynamics of basal motion in glacier models and analyses. If these findings are generalizable, they suggest that declining basal motion reduces the flux of ice to lower elevations, helping to mitigate glacier mass loss in a warming climate. Plain Language Summary: Changes in glacier speed affect how glaciers react to climate change. Sliding at the base of a glacier is sensitive to meltwater lubrication, and this process allows glaciers to respond rapidly to climate warming. We use data of ice thickness and ice flow speed from the 1960s on a well‐studied Canadian glacier and compare these data to modern values. We find that the glacier has thinned and slowed, though its surface has steepened in most places. We apply a simplified ice flow model to investigate the mechanisms responsible for glacier slowing and find that a decline in sliding at the glacier base is the dominant process. We then utilize simplified models of glacier sliding and water flow to show that the glacier base has become stickier, likely due to changes in the shape of the glacier as well as its ability to drain water. These findings are important because they show how sliding at the base of a glacier changes over >50‐year timespans, which can impact the glacier's long‐term health. If the reduced sliding we detect at this glacier is a common phenomenon, it could have a stabilizing effect on the world's glaciers in response to anthropogenic climate change. Key Points: Steepening counteracts thinning at Athabasca Glacier, resulting in minimal driving stress reduction. Surface velocity slowed by 15 m/a (45%) The slowdown is primarily attributable (91%) to decreasing basal motion, which cannot be described with a time constant friction parameter Changes in glacier geometry and subglacial hydrology likely drive the glacier's basal friction increase and basal motion decrease